The Role of Omega-3 Fatty Acids in Mitigating Metabolic Risk Factors Associated with Alzheimer's Disease: A Systematic Review and Meta-Analysis - Agustinus I Wayan Harimawan; Cuay Yusnianingsih; Anak Agung Sagung Mirah Prabandari (Bali Medical and Wellness Journal, 2025)
Background: Alzheimer’s disease (AD) is linked to metabolic conditions like obesity and hypertension, which share inflammation and oxidative stress as common factors. Omega-3 fatty acids (EPA and DHA) may have neuroprotective and anti-inflammatory benefits. Objective: This study aims to review the effectiveness of omega-3 supplements in reducing metabolic risk factors and slowing cognitive decline in people with AD. Methods: Following PRISMA guidelines, a comprehensive search was conducted in PubMed, ScienceDirect, and Google Scholar for randomized controlled trials (RCTs) published until July 2025. Eligible studies included older adults (≥65 years) with AD or mild cognitive impairment (MCI) and assessed the impact of omega-3 supplements on cognitive and/or metabolic outcomes. The risk of bias was evaluated using the Cochrane ROB-2 tool. Data were analyzed with Review Manager 5.4 using fixed-effects models for continuous outcomes. Results: Five RCTs with a total of 490 participants were included. Meta-analysis of four trials (326 participants) revealed that omega-3 supplementation significantly improved Mini-Mental State Examination (MMSE) scores compared to placebo (mean difference: 0.21; 95% CI: 0.02–0.41; P = 0.03; I² = 0%). No significant effects were found for ADAS-Cog scores (mean difference: 0.11; 95% CI: –0.40 to 0.62; P = 0.68; I² = 46%) or IADL scores (mean difference: 0.48; 95% CI: –0.17 to 1.13; P = 0.15; I² = 36%). Conclusion: Omega-3 fatty acids may offer modest cognitive benefits in AD, though heterogeneity among studies limits general conclusions. Future well-designed RCTs should consider metabolic profiles and standardized dosing to identify populations most likely to benefit from omega-3 supplementation.